Innovative Approaches In Management To Support Organizational Sustainability - Sukarman, Silaja (Smart International Management Journal, 2024)
Abstract Effective management is key to organizational success in facing global challenges. This article explores modern management theories and practices with a focus on innovative approaches that support organizational sustainability. By utilizing case studies and theoretical analysis, it can provide insights into the importance of strategic management, human resources, and change management. Innovative approaches in management play a crucial role in supporting organizational sustainability amidst changing market dynamics. Organizations that are able to adapt and integrate innovation into their managerial strategies can not only increase competitiveness but also build the foundation for long-term sustainability. This approach includes the application of new technologies, the development of products and services that are responsive to market needs, and the implementation of flexible and inclusive managerial practices. Innovation in management also involves managing human resources more effectively, through employee empowerment and an organizational culture that encourages creativity and collaboration. By adopting innovative approaches, organizations can create added value, strengthen relationships with stakeholders, and achieve sustainability goals that focus not only on economic benefits, but also social and environmental aspects. Therefore, the application of innovation in management is key to ensuring the continuity and growth of organizations in facing increasingly complex global challenges. Keywords: Innovative Approach, Management, Organizational Sustainability, Innovation, Competitive Advantage, Human Resources, Risk Management, Shared Value, Social Responsibility, Environmental Impact.